Highly enhanced chiroptical effect from self-inclusion helical nanocrystals of tetraphenylethylene bimacrocycles - Hu, Ming; Ye, Feng-Ying; Yu, Wei; Sheng, Kang; Xu, Zhi-Rong; Fu, Jin-Jin; Wen, Xin; Feng, Hai-Tao; Liu, Minghua; Zheng, Yan-Song (Chemical science (Cambridge), 2024)
The helical structure is often the key factor for forming and enhancing chiroptical properties, such as circular dichroism (CD) and circular polarized luminescence (CPL) effects. However, no matter whether helical molecules or helical aggregates, they usually display modest chiroptical signals, which limits their practical applications. Herein, chiral tetraphenylethylene (TPE) bimacrocycles prepared in almost quantitative yield show strong and repeatable CD signals up to more than 7000 mdeg, which is very rare for general organic compounds, besides emitting very strong CPL light with an absolute g lum value up to 6.2 × 10 −2 . It is found that the superhelices formed by self-inclusion between the cavity and outward cyclohexyl ring of TPE bimacrocycles in crystal state are the key factor for highly enhanced chiroptical effect, and the self-inclusion superhelices in assemblies are confirmed by High Resolution Transmission Electron Microscopy (HR-TEM), Powder X-ray Diffraction (XRD) and Fourier Transform Infrared Spectrometry (FT-IR) data. Furthermore, the chiral TPE bimacrocycle shows great potential in chiral recognition and chiral analysis not only for chiral acids but also for chiral amines, chiral amino acids, and neutral chiral alcohol. Using self-inclusion helical nanocrystals of chiral macrocycles, this work provides a new strategy for chiroptical materials with excellent chiroptical properties. New chiral TPE bimacrocycles exhibit helical self-inclusion in crystals, strong CD (>7000 mdeg) and CPL (absolute g lum 0.062) signals, and significant potential in enantiomer analysis for diverse chiral molecules.